THE CONTEXTS OF THE STUDENT TAKING THE MICRO TEACHING CLASS - Julie, Hongki (Sanata Dharma University Yogyakarta, 2017)
In this paper, the researcher would only present the results obtained by the researcher related to the context of students. To find out the context of the students who took this course, the researcher did the taking: (1) find the students’ hometown data and the students’ GPA from the Sanata Dharma Academic Information System (SDAIS), and (2) make a questionnaire consisting of four questions filled by students at the first meeting. The results of this research was as follows: (1) ten students came from Java Island and nine students came from outside Java Island, (2) six students had GPA above 3.00 and thirteen students had GPA below 3.00, (3) eleven students said that their vocation was to be a teacher when they first chose this program, (4) there were 13 students who experience change of vocation, and (5) there were eighteen students who stated that their obstacles in taking this lecture were “I had not